New Dynamic Channel Allocation Algorithms - Shinoda, Ailton A.; Yacoub, Michel D. (Journal of Communication and Information Systems, 2017)
A set of tbree allocation algorithms is proposed and analysed. As opposed to a number of allocation algorithms, whose performance is greatly dependent on the traffic profile, these techniques are dynamically adaptable to the change of the traffic load, combining the features of dynamic channel allocation and fixed channel allocation, migrating smoothly from one to another technique to give the best performance in any circumstances. Although the proposed strategies assign the channels in a fully dynamic fashion, this is carried out in a disciplined way so that channels are packed into reuse groups and the reuse distance is kept to a minimum, increasing the reuse efficiency.